2016
DOI: 10.1007/s00192-016-3144-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of voiding dysfunction following extensive vaginal pelvic reconstructive surgery

Abstract: Diabetes mellitus, concurrent midurethral sling insertion, preoperative Dmax <10 cm HO and postvoid residual volume ≥200 ml in patients with advanced pelvic organ prolapse were risk factors for the development of postoperative voiding dysfunction after vaginal pelvic reconstructive surgery. Therefore, counseling is worthwhile before considering vaginal pelvic reconstructive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 25 publications
0
36
0
1
Order By: Relevance
“…Moreover, concomitant MUS surgery was not associated with a higher risk of voiding dysfunction. In contrast, previous studies have reported a significantly increased risk of voiding dysfunction after MUS concomitant with mesh surgery 19,20 and determined risk factors for voiding dysfunction as diabetes mellitus, detrusor pressure at maximal flow <10 cm H 2 O and postvoid residual more than 200 mL.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, concomitant MUS surgery was not associated with a higher risk of voiding dysfunction. In contrast, previous studies have reported a significantly increased risk of voiding dysfunction after MUS concomitant with mesh surgery 19,20 and determined risk factors for voiding dysfunction as diabetes mellitus, detrusor pressure at maximal flow <10 cm H 2 O and postvoid residual more than 200 mL.…”
Section: Discussionmentioning
confidence: 76%
“…However, the overall incidence of postoperative voiding dysfunction was only 3.5% and 1% developed de novo voiding dysfunction . A detrusor pressure at maximal flow <10 cmH2O found in 3% of the women was the only urodynamic covariate associated with postoperative voiding dysfunction (OR 1.8) . Concurrent MUS insertion was also associated with a higher risk of postoperative voiding dysfunction (OR 3.1) .…”
Section: Discussionmentioning
confidence: 99%
“…One might be reluctant to perform prophylactic incontinence surgery in women with detrusor underactivity or voiding dysfunction. Lo et al found in a considerable number of women with advanced prolapse a sign of bladder outlet obstruction. However, the overall incidence of postoperative voiding dysfunction was only 3.5% and 1% developed de novo voiding dysfunction .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations